Understanding Linguistics: A Simplified Introduction to the Scientific Study of Language - Ali Abdulhamzah Abdul. Z (International Journal Of Literature And Languages, 2025)
Linguistics is a modern field of science that seeks to understand language as a uniquely human phenomenon. In Understand Linguistics, the subject is presented in a clear and comprehensive way, making it accessible to non-specialist readers who wish to gain a general understanding of this vital discipline. The book covers several major themes that form the core foundations of linguistics, including: